Development of Character Education in the PAUD Curriculum through Getting Used to Simplified Kromo Javanese at the SELASIH Banyuwangi Kindergarten - kirstini kristini (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2023)
This research aims to determine the character cultivation program for early childhood through familiarization with simple Javanese Kromo language for early childhood at Selasih Kindergarten, Grajagan Village, District. Purwoharjo, Banyuwangi Regency. In practice, this habituation program is carried out on a scheduled or incidental basis every day. In this research, the method used is a qualitative method through general steps, namely problem identification, planning, implementation, reporting and follow-up. Overall, the results of this research show that the simple Javanese Kromo language familiarization program at the SELASIH Purwoharjo Banyuwangi Kindergarten can form students' attitudes of character and love of the homeland through the introduction and habituation of local culture, one of which is simple Javanese language culture for PAUD children. The character that is formed is language, polite attitudes and behavior towards friends, teachers and parents as well as love for one's culture. In its implementation, support from teachers, teaching programs, and parents is the key to success in implementing this habituation activity program. Because PAUD children are great imitators, PAUD teachers must be models who are able to teach character values regarding language and polite and polite behavior in daily learning activities.